By His Excellency, Thomas Chittenden, Esquire ... A proclamation : ... I do hereby appoint, Wednesday the twenty-seventh day of April next, to be observed as a day of public fasting, humiliation and prayer ... Given under my hand at Arlington, this twenty-fourth day of March, in the year of our Lord, one thousand seven hundred and eighty-five . (1785)
March 24, 1785 Proclamation by Governor Thomas Chittenden setting April 27th as a day of public fasting, humiliation and prayer in the state.